Activity and determinants of cholinesterases and paraoxonase-1 in blood of workers exposed to non-cholinesterase inhibiting pesticides. (25th November 2016) - Lozano-Paniagua, David; Gómez-Martín, Antonio; Gil, Fernando; Parrón, Tesifón; Alarcón, Raquel; Requena, Mar; Lacasaña, Marina; Hernández, Antonio F.
Abstract: Pesticide exposure has been associated with different adverse health effects which may be modulated to some extent by paraoxonase-1 (PON1) activity and genetic polymorphisms. This study assessed seasonal variations in PON1 activity (using paraoxon –POase–, phenylacetate –AREase–, diazoxon –DZOase– and dihydrocoumarin –DHCase– as substrates), erythrocyte acetylcholinesterase (AChE) and plasma cholinesterase (using butyrylthiocholine –BuChE– and benzoylcholine –BeChE– as substrates. The study population consisted of intensive agriculture workers regularly exposed to pesticides other than organophosphates and non-exposed controls from Almería (Southeastern Spain). The effect of common genetic polymorphisms of PON1 and BCHE on paraoxonase-1 and cholinesterase activities toward different substrates was also assessed. Linear mixed models were used to compare esterase activities in agricultural workers and control subjects over the two study periods (high and low exposure to pesticides). The significant decrease in AChE and increase in BuChE and BeChE activities observed in workers with respect to control subjects was attributed to pesticide exposure. Workers also had higher levels of AREase, DZOase and, to a lesser extent, of POase, but showed decreased DHCase activity. While PON1 Q192R and PON1 -108C/T gene polymorphisms were significantly associated with all PON1 activities, PON1 L55M showed a significant association with AREase, DZOase and DHCase. BCHE-K (Karlow variant) was significantly associated with lower BeChE activity (but not with BuChE) and BCHE-A (atypical variant) showed no significant association with any cholinesterase activity. These findings suggest that increased PON1, BuChE and BeChE activities in exposed workers might result from an adaptive response against pesticide exposure to compensate for adverse effects at the biochemical level. This response appears to be modulated by PON1 and BCHE gene polymorphisms.